Integrating Traditional Games into Literacy Instruction: The Development of 'Cak Ingkling' Media for Early Reading Skills - Yuniarti; Leni Pebriantika; Heni Rita Susila (Sakura Digital Nusantara, 2026)
Early literacy skills form the cornerstone of academic success, yet many first-grade students in primary schools struggle with foundational reading competencies due to limited access to contextual learning media. This research aimed to develop a non-digital, game-based learning medium called “Cak Ingkling” and evaluate its validity, practicality, and pedagogical potential for lower-grade primary school classrooms. The study employed a Research and Development (R&D) methodology using the ADDIE model integrated with Tessmer’s formative evaluation framework, spanning expert review, one-to-one, small group, and field testing phases. Data were gathered through validation sheets, user questionnaires, and structured observations. Evaluation results confirmed high feasibility: content validation reached 87.2% (Excellent), instructional design scored 84.2% (Good), and media expert validation achieved 87.3% (Excellent). Classroom field trials with first-grade students produced an overall practical and positive user response score of 87.2% (Excellent). The study concludes that the “Cak Ingkling” learning medium, as a culturally responsive innovation, shows strong potential as a valid and practical instructional tool for fostering student participation and supporting early reading engagement in resource-constrained primary school settings, although measurable reading achievement gains remain to be empirically tested through future longitudinal experimental designs.